DIGITAL MARKETING IN THE AGE OF ARTIFICIAL INTELLIGENCE: OPPORTUNITIES AND CHALLENGES (Web of Teachers: Inderscience Research, 2025)
Our article is dedicated to the study of the impact of artificial intelligence (AI) on digital marketing. In recent years, AI has significantly transformed approaches to advertising, sales, and customer interactions, opening up new opportunities for personalization and optimization of marketing strategies. The article examines key AI technologies such as machine learning, big data processing, chatbots, and consumer behavior prediction